Multicountry research on comprehensive abortion policy implementation in Latin America: A mixed-methods study protocol - Gialdini, Celina (2024)
Introduction Access to comprehensive abortion carecould prevent the death of between 13 865 and 38940 women and the associated morbidity of 5 millionwomen worldwide. There have been some importantimprovements in Latin America in terms of lawsand policies on abortion. However, the predominantenvironment is still restrictive, and many women,adolescents and girls still face multiple barriers toexercise their reproductive rights. This research willsystematically assess comprehensive abortion policiesin five Latin American countries (Argentina, Colombia,Honduras, Mexico and Uruguay). The aim is to identifybarriers, facilitators and strategies to the implementationof abortion policies, looking at four key dimensions—regulatory framework, abortion policy dynamics, abortionservice delivery and health system and health outcomesindicators—to draw cross-cuttinglessons learnt toimprove current implementation and inform future safeabortion policy development.Methods and analysis A mixed-methoddesign will beused in the five countries to address the four dimensionsthrough the Availability, Accessibility, Acceptability andQuality of Care model. The data collection tools includedesk reviews and semi-structuredinterviews with keyactors. Analysis will be performed using thematic analysisand stakeholder analysis. A regional synthesis exercise willbe conducted to draw lessons on barriers, facilitators andthe strategies.Ethics and dissemination The project has beenapproved by the WHO Research Ethics Review Committee(ID: A66023) and by the local research ethics committees.Informed consent will be obtained from participants.Data will be treated with careful attention to protectingprivacy and confidentiality. Findings from the study willbe disseminated through a multipurpose strategy totarget diverse audiences to foster the use of the studyfindings to inform the public debate agenda and policyimplementation at national level. The strategy will includeacademic, advocacy and policy arenas and actors,including peer-reviewedpublication and national andregional dissemination workshops.